Homeless and marginally housed Veteran perspectives on participating in a photo-elicitation research study - Keri Rodriguez (The Beryl Institute, 2018)
Photo-elicitation interviewing (PEI) seems a valuable tool for engaging marginalized populations in research despite documented challenges. Given limited data on acceptability of PEI among homeless and marginally housed Veterans, this evaluation aimed to characterize their research experience. Veterans took photographs about health, health behaviors, and health care which facilitated semi-structured interviews. Their research study experience was assessed via a modified Reactions to Research Participation Questionnaire-Revised (RRPQ-R), along with additional survey and open-ended questions. Of the 20 participants who consented and participated, 16 (80%) completed the exit surveys. Most participants (>88%) indicated favorable experiences and limited drawbacks. Respondents disagreed that participation was difficult or overly time consuming. Many indicated intense or unexpected emotionality. Open-ended responses indicated appreciation of photography, interview experiences, and connection with study staff. Transportation was the most cited barrier. Overall, experiences were reportedly emotionally challenging, but positive. PEI appears to be acceptable to homeless and marginally housed Veterans for eliciting their perspectives.